2010
DOI: 10.1186/1472-6823-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism among military infants born in countries of varied iodine nutrition status

Abstract: BackgroundIodine deficiency is a global problem representing the most common preventable cause of mental retardation. Recently, the impact of subtle deficiencies in iodine intake on children and pregnant women has been questioned. This study was designed to compare hypothyroidism among infants born to US military families in countries of varied iodine nutrition status.MethodsA cohort design was used to analyze data from the Department of Defense Birth and Infant Health Registry for infants born in 2000-04 (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Iodine deficiency or excess (18,26,34), gender (31,17), seasonality (5, 13, 20-22, 30, 67) maternal age (12,37,44,61,63), type of delivery (28,62) and maternal anti-thyroid drug use (6,27) were the risk factors with controversial reports. Though their role as CH-related risk factors has been demonstrated in previous studies, the findings are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine deficiency or excess (18,26,34), gender (31,17), seasonality (5, 13, 20-22, 30, 67) maternal age (12,37,44,61,63), type of delivery (28,62) and maternal anti-thyroid drug use (6,27) were the risk factors with controversial reports. Though their role as CH-related risk factors has been demonstrated in previous studies, the findings are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported advanced maternal age as a risk factor for CH (12,37,44). But some of them have reported such an association only for thyroid dysgenesis (64).…”
Section: Discussionmentioning
confidence: 99%
“…Low socio‐economic status, another prognostic factor, was controlled for by using Medicaid enrollment as a proxy measure. We used the CCS and published literature to identify ICD‐9‐CM codes for the comorbidities . Claims data from the 365‐day pre‐index period were reviewed to identify covariate information.…”
Section: Methodsmentioning
confidence: 99%
“…We used the CCS and published literature to identify ICD-9-CM codes for the comorbidities. 23,[40][41][42][43] Claims data from the 365-day pre-index period were reviewed to identify covariate information.…”
Section: Covariate Measuresmentioning
confidence: 99%
“…Increased T3 which is metabolically efficient, but requires less iodine is the organism's defense against iodine deficiency. Iodine deficiency causes to increased TSH release in the newborn (12)(13)(14)(15)(16)(17).…”
Section: Inroductionmentioning
confidence: 99%